A longitudinal study investigating positive body image, eating disorder symptoms, and other related factors among a community sample of men in the UK. (June 2022) - Alleva, Jessica M.; Paraskeva, Nicole; Craddock, Nadia; Stuijfzand, Bobby G.; Diedrichs, Phillippa C.
Abstract: Emerging research suggests that positive body image —an overall love and respect for one's body— may be a protective factor for eating disorder (ED) symptoms. This study aimed to explore the relationships between positive body image, ED symptoms, and related factors among men across time. A community sample of 440 British men completed questionnaires at Time 1 and Time 2 (1 year later). Linear models showed that, unexpectedly, positive body image at Time 1 did not predict change in ED symptoms at Time 2, and ED symptoms at Time 1 did not predict change in positive body image at Time 2. However, positive body image at Time 1 did predict increased appearance satisfaction and decreased appearance-ideal internalisation at Time 2. Increased positive body image at Time 2 was only predicted by appearance satisfaction at Time 1. Although no evidence for a longitudinal relationship between positive body image and ED symptoms was found, positive body image did predict change in established risk factors for disordered eating among men. Future research on positive body image and eating behaviour among men could be improved by including assessments of muscularity-oriented and adaptive eating behaviours. Highlights: We investigated positive body image (PBI) and eating disorder symptoms (EDS) among British adult men. Findings do not support a bidirectional relationship between PBI and EDS. Findings show a bidirectional relationship between PBI and appearance satisfaction. PBI also predicted decreased appearance-ideal internalisation.